The Influence of Service Quality on Customer Satisfaction at PT BBRS Al-Washliyah Medan - Syahputra, Reza; Maryam Batubara (Universitas Islam Negeri Alauddin Makassar, 2025)
In the era of increasingly fierce banking competition, service quality is one of the factors that determine the success of a financial institution. This research aims to determine the influence of service quality on customer satisfaction at PT BPRS Al-Wasliyah Medan. This research was conducted on customers of PT BPRS Al-Wasliyah Medan. The type of research used is quantitative research. Sampling used the Purposive Sampling technique, because the researcher only sampled 91 customer respondents. The data collection technique uses a questionnaire whose validity and reliability have been tested. From the findings of the research conducted, it shows that Service Quality, namely, Reliability, Responsiveness, Empathy, Assurance, Tangible is very influential on customer satisfaction of PT BPRS Al-Wasliyah Medan. With a coefficient of determination (adjusted R square) of 0.713 or 71.3%. By improving service quality customer pleasure or satisfaction is fulfilled.